The Influence of Arts Education on Creativity and Innovation in Community Development - Hartatik Hartatik; Arief Yanto Rukmana; Loso Judijanto; Alfa Santoso Budiwidjojo Putra (Westscience Press, 2023)
This research conducts a comprehensive bibliometric analysis to explore the effect of arts education on creativity, innovation, and community development. Drawing upon key citations, thematic clusters, and the frequency of terms within the literature, the study provides a nuanced understanding of the theoretical foundations and practical implications within this dynamic field. Thematic clusters reveal diverse dimensions, ranging from the economic aspects of tourism to the educational dimensions of university-community relationships. Key citations, including seminal works by Dewey, Knowles, and Greene, contribute to the theoretical framework, emphasizing experiential learning, andragogy, and the transformative potential of arts education in driving social change. The frequency of terms underscores the centrality of learning and participation while also recognizing the relational, ethical, and conceptual dimensions within the discourse. Practical implications for educators, practitioners, and policymakers are discussed, highlighting the importance of active community engagement, sustainable development, and the transformative role of arts education. The synthesis of findings offers a roadmap for future research, guiding scholars and practitioners in exploring innovative pedagogies, longitudinal impacts, demographic considerations, and global perspectives within the evolving landscape of arts education and community development.